Alcohol misuse, risky sexual behaviors, and HIV or syphilis infections among Chinese men who have sex with men. (1st November 2016) - Liu, Yu; Ruan, Yuhua; Strauss, Shiela M.; Yin, Lu; Liu, Hongjie; Amico, K. Rivet; Zhang, Chen; Shao, Yiming; Qian, Han-Zhu; Vermund, Sten H.
Highlights: Alcohol use and misuse remains a critical challenge among Chinese men who have sex with men (MSM). Binge/hazardous drinking Chinese MSM are more likely to conduct high-risk behaviors. Binge/hazardous drinking Chinese MSM are associated with higher HIV risk. As AUDIT-C score increases, probabilities of HIV/syphilis infection also increase. Abstract: Background: Few studies have employed standardized alcohol misuse measures to assess relationships with sexual risk and HIV/syphilis infections among Chinese men who have sex with men (MSM). Methods: We conducted a cross-sectional study among MSM in Beijing during 2013–2014. An interviewer-administered survey was conducted to collect data on sociodemographics, high-risk behaviors, and alcohol use/misuse patterns (hazardous/binge drinking and risk of alcohol dependence) in the past 3 months using Alcohol Use Disorder Identification Test-Consumption (AUDIT-C). We defined AUDIT-C score ≥4 as recent hazardous drinkers, and drinking ≥6 standard drinks on one occasion as recent binge drinkers. Results: Of 3588 participants, 14.4% reported hazardous drinking, 16.8% reported binge drinking. Hazardous and binge drinking are both associated with these factors ( p < 0.05): older age, being migrants, living longer in Beijing, township/village origin, being employed, higher income, self-perceived low/no HIV risk, and sex-finding via non-Internet venues. Hazardous (vs non-hazardous) or binge (vs. non-binge) drinkers were more likely to use illicit drugs, use alcohol before sex, have multiple partnerships, pay for sex, and have condomless insertive anal intercourse. MSM who reported binge (AOR, 1.34, 95% CI, 1.02–1.77) or hazardous (AOR, 1.36, 95% CI, 1.02–1.82) drinking were more likely to be HIV-infected. MSM at high risk of current alcohol dependence (AUDIT-C ≥8) were more likely to be HIV- (AOR, 2.37, 95% CI, 1.39–4.04) or syphilis-infected (AOR, 1.96, 95% CI, 1.01–3.86). Conclusions: Recent alcohol misuse was associated with increased sexual and HIV/syphilis risks among Chinese MSM, emphasizing the needs of implementing alcohol risk reduction programs in this population.